Penguatan Self-Efficacy dan Self-Esteem siswa SMA Laboratorium UM dalam meraih prestasi - Karkono Karkono; Evynurul Laily Zen; Rully Aprilia Zandra; Moh Safii; Bunga Almia Gane Sari; Luthfi Farihatun Nisa’ (Universitas Hamzanwadi, 2022)
Students at school need to be encouraged to continue to think creatively and be able to solve the problems they face entirely. They need encouragement from within and especially from outside, namely through the school environment or their parents, so that positive attitudes and self-confidence can grow so they can solve various challenges. This training aims to give students some skills, so they are more confident and have a highly competitive spirit. This training has three phases: the first phase of sharing and motivation to increase self-efficacy and self-esteem; the second phase of sharing competition events to increase the spirit of competition; and the third phase of a scientific paper presentation festival to foster self-confidence. This training was held as planned for self-efficacy and self-esteem training on June 17–20, 2022. The second activity was the student competition-sharing event held on July 21, 2022, and the Scientific Writing Presentation Festival was held on November 25, 2022. The dedication results showed 56.5% expressed satisfaction, while the rest were delighted. This service succeeded in increasing students' self-esteem and self-efficacy. They were also supported by the readiness of students to enter the world of higher education through the advice given